2017
DOI: 10.1177/0267323117695736
|View full text |Cite
|
Sign up to set email alerts
|

Impartiality, statistical tit-for-tats and the construction of balance: UK television news reporting of the 2016 EU referendum campaign

Abstract: There has been greater news industry recognition in recent years that impartiality should not be translated into simply balancing the competing sides of a debate or issue. The binary nature of a referendum campaign represents a unique moment to consider whether broadcasters have put this into practice beyond routine political reporting. This study examines how impartiality was editorially interpreted in television news coverage during the United Kingdom’s 2016 European Union referendum. We carried out a system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 7 publications
0
30
0
1
Order By: Relevance
“…Our research on the broadcast coverage of the referendum campaign (Cushion and Lewis 2016) suggests that the reporting of the campaign was an exemplar of precisely the problems addressed by the review. Rather than seizing the opportunity to address the United Kingdom's considerable democratic deficit in understanding the European Union and establishing a knowledge base for assessing arguments for and against membership, broadcasters tended to reproduce what was widely regarded as an unhelpful series of claims and counter-claims.…”
Section: Interpreting Statistical Claims: Towards More Clarity and Inmentioning
confidence: 97%
See 1 more Smart Citation
“…Our research on the broadcast coverage of the referendum campaign (Cushion and Lewis 2016) suggests that the reporting of the campaign was an exemplar of precisely the problems addressed by the review. Rather than seizing the opportunity to address the United Kingdom's considerable democratic deficit in understanding the European Union and establishing a knowledge base for assessing arguments for and against membership, broadcasters tended to reproduce what was widely regarded as an unhelpful series of claims and counter-claims.…”
Section: Interpreting Statistical Claims: Towards More Clarity and Inmentioning
confidence: 97%
“…While most of the statistical evidence tended to support claims on the "Remain" side of the argument, claims and counter-claims were routinely balanced without any clear sense that one had greater validity (Cushion and Lewis 2016). Given the closeness of the result and its weighty consequences, the lack of prominent independent scrutiny of claims made by the "Leave" campaign (many of which rapidly unravelled after the vote) might be seen to have been a significant part of its success.…”
Section: Data Journalism Impartiality and Statistical Claims 1207mentioning
confidence: 99%
“…Furthermore, considering the often rancorous nature of referendum arguments, in which many of the statistical claims were selectively reported (Nakatudde, 2017) and presented in tit-for-tat exchanges between rival referendum camps (Cushion & Lewis, 2017), it is additionally important to explore the roles of cognitive biases such as ideologically motivated reasoning, ideologically motivated numeracy, framing, and the DunningKruger effect. In particular, it would be useful to understand if one set of voters were more susceptible to these biases than the other.…”
Section: Numeracy Thinking Styles and Cognitive Biasesmentioning
confidence: 99%
“…That is, given the quantity of numerical and non-numerical data published about the EU and associated topics, the ability to accurately evaluate the data is of high importance in making informed decisions. Referendum campaigns and accompanying analysis not only featured numerical data, but a high velocity of numerical data covering a range of topics over a number of months, often in the form of tit-for-tat exchanges (Cushion & Lewis, 2017). It could be argued that voters were bombarded with an overwhelming and bewildering amount of numerical information.…”
Section: Thinking Stylesmentioning
confidence: 99%
“…Research on the broadcast coverage of the EU campaign, for example, found broadcasters often reported the tit-for-tat exchanges between THINK TANKS, TELEVISION NEWS AND IMPARTIALITY 481 politicians, with statistics traded back and forth, with little evidentiary commentary or mediation. This made it hard for audiences to assess where the weight of evidence lay (Cushion and Lewis 2017). The study also found that while broadcasters were successful in balancing Leave and Remain points of view, they did not feel compelled to underscore this with a sense of party political balance.…”
Section: Justin Lewis and Stephen Cushionmentioning
confidence: 93%